Μελέτη της αντιοξειδωτικής ικανότητας των τοκοχρωμανολών : ο ρόλος της θερμοκρασίας και του διαλύτη - Αναστασίου, Μάριος (Σχολή Γεωτεχνικών Επιστημών και Διαχείρισης Περιβάλλοντος, Τμήμα Γεωπονικών Επιστημών, Βιοτεχνολογίας και Επιστήμης Τροφίμων, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2015)
Vitamin E refers to a group of compounds that include both tocopherols and tocotrienols. They are mostly found in fats and oils, which have both health-promoting and antioxidant properties. The intake of tocochromanols is important, since it is an antioxidant that stabilizes the free radicals generated by stress. DPPH radical scavenging activity is often used to determine the in vitro antioxidant activity of fruit, vegetables and foods of plant origin. The objective of the present study was to investigate structure-activity relationship of tocochromanols. Furthermore, the effect of aprotic and protic solvents and the tempearature on the reaction between DPPH radical and tocopherols was determines. Results showed that the antioxidant activity of tocochromanols was strongly affected by their chemical structures. In general, tocotrienols are more potent antioxidants than tocopherols. The latter is attributed to the presence of double bonds in the aliphatic chain. The antioxidant activity of tocochromanols is also influenced by the number and position of methyl groups onto aromatic ring. Overall, α-tocotrienol was the strongest antioxidant among tocochromanols, whereas α-tocopherol had the most weak antioxidant potency. Regarding to the temperature, the rate of the reaction between DPPH radical and α-tocopherol was affected by the temperature. The rate of reaction increased as the temperature was raised. However, the boiling point of solvent and the stability of tocochromanols at high temperature are critical points for this reaction. Results also demonstrated a significant effect of solvent on estimated antioxidant activity. In particular, the use isobutanol as solvent gave the highest values of antioxidant activity. On the other hand, the use of dimethyl sulfoxide led to the underestimation of antioxidant activity of tocopherols. Solvent properties such as the ability to form hydrogen bonds with the tocochromanols as well as the solubility of tocochromanols in solvents seem to influence the level of estimated antioxidant activity. Overall, the tocochromanol diversity, their concentration, the temperature and the solvent properties influence the estimated antioxidant activity of foods with plant origin such food, vegetables, functional foods etc.
Keywords: Tocopherols; Tocotrienols; Antioxidant activity; Temperature; Aprotic and protic solvents; DPPH radical; Τοκοφερόλες; Τοκοτριενόλες; Αντιοξειδωτική ικανότητα; Ρίζα DPPH; Πρωτικοί και απρωτικοί διαλύτες; Θερμοκρασία